Path Optimization based on Bit Error Rate (BER) Estimation in Underwater Sensor Networks - Madhumita, S; Niranjana, G; M. Shenbagaraman, V (International Journal of Engineering and Technology, 2018)
The underwater sensor networks (UWSNs) is an enabling technology and has become more and more trend for detecting vast area of oceans. Underwater sensor Networks consist of a variable number of sensors based on acoustic wireless communications. Communications are rapidly used for enabling advances in terms of ocean monitoring and observatory systems, deep sea surveillance and tracking of various entities of the aquatic environment and unearthing resources. But the drawback of the existing system is load and latency. Our proposed work mainly aimed to increase the throughput and optimize the path based upon relay node selection using BER estimation. And the performance of the system is analyzed using mathematical and simulation methods by comparing parameters such as Energy consumption , throughput, End to end delay.Â Â